DEVELOPMENT COMMUNICATION AND PUBLIC INFORMATION TRANSPARENCY: A CONTENT ANALYSIS OF THE WEBSITE OF THE BIREUEN REGENCY GOVERNMENT - Nurhayati Nurhayati; Irhazt Angga Denilza; Syifa Urrahmah; Ramayuni Ramayuni (Program Pascasarjana UIN Sumatera Utara, 2026)
The rapid growth of digital technology has encouraged local governments to utilize online platforms as tools for development communication and public information dissemination. Government websites serve as strategic spaces for demonstrating accountability, providing development data, and strengthening engagement with citizens. However, the effectiveness of such platforms depends not only on the availability of information but also on the depth, clarity, and transparency of the messages presented. Within this context, this study explores how the Government of Bireuen Regency represents development communication and public information transparency through its official website from May to October 2025. Using qualitative content analysis guided by Krippendorff's framework, the research examines news articles, announcements, opinion pieces, and activity reports collected through systematic observation and documentation. The findings show that the government frequently employs positive, ceremonial, and legitimacy-oriented framing, particularly in topics related to social housing, participatory planning, budget refocusing, and educational revitalization. Although the website structure is well-organized, the transparency offered remains symbolic, with limited quantitative data, progress indicators, and technical details. These results highlight the need to strengthen substantive transparency through open data and participatory mechanisms so that the website can function as an effective instrument of public accountability